2007
DOI: 10.1088/1748-6041/2/3/s16
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a FGF-2 and calcium phosphate composite layer on a hydroxyapatite ceramic for promoting bone formation

Abstract: Fibroblast growth factor-2 (FGF-2) was immobilized on a hydroxyapatite (HAP) ceramic in supersaturated calcium phosphate solution prepared using solutions corresponding to clinically approved infusion fluids. To avoid the risk of FGF-2 denaturation, FGF-2 immobilization was carried out at 25 degrees C. FGF-2 was successfully immobilized on HAP ceramic surfaces by deposition with calcium phosphate to form a FGF-2 and calcium phosphate composite layer. A maximum of 2.72 +/- 0.01 microg cm(-2) of FGF-2 was immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Such improvement includes surface modifications to enhance biocompatibility and osteoconductivity with the use of calcium phosphates, TiO 2 −strontium−CaSiO 3 −biopolymer composite, acid-etching, zinc-modified Ca−Si ceramic, and CaTiSiO 5 ceramic [512]. Moreover, biologically active molecules such as fibroblast growth factor-2 (FGF-2), bone morphogenetic proteins (BMP), collagen, fibronectin, 1,25-vitamin D 3 , semaphorin 3A, and bisphosphonate are combined with the surface or incorporated into osteoconductive coatings [11, 1320]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such improvement includes surface modifications to enhance biocompatibility and osteoconductivity with the use of calcium phosphates, TiO 2 −strontium−CaSiO 3 −biopolymer composite, acid-etching, zinc-modified Ca−Si ceramic, and CaTiSiO 5 ceramic [512]. Moreover, biologically active molecules such as fibroblast growth factor-2 (FGF-2), bone morphogenetic proteins (BMP), collagen, fibronectin, 1,25-vitamin D 3 , semaphorin 3A, and bisphosphonate are combined with the surface or incorporated into osteoconductive coatings [11, 1320]. …”
Section: Introductionmentioning
confidence: 99%
“…Apatite is an osteoconductive material that is widely used in orthopedic and maxillofacial surgery [57]. The FGF-2−apatite composite layers form during immersion of the screws in infusion fluid-based supersaturated calcium phosphate solutions containing FGF-2 [13, 25, 26]. FGF-2 co-precipitates with calcium phosphate and consequently can be incorporated into the apatite layer.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-sprayed apatite coating has increased the extraction torque of various external fixation pins by 53%–124% compared with that of uncoated pins [10,11]. Other approaches to form an apatite coating include those using supersaturated calcium phosphate (CaP) solutions [1521]. Conventional supersaturated solution methods have been generally two-step techniques composed of a physicochemical modification step of substrates and an immersion step in a supersaturated CaP solution prepared from chemical reagents [1719].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This biomolecule-CaP affinity provides a potentially universal tool to efficiently incorporate within delivery carriers. Indeed, previous results have shown that growth factors, including bone morphogenetic protein 2 (BMP-2), 15 transforming growth factor-beta 1 (TGF-b1), 16 insulin-like growth factor 1 (IGF-1), 17 and fibroblast growth factor 2 (FGF-2), 18 and other therapeutic agents, such as metal ions for antimicrobial purposes, 19,20 can be surface bound during the formation of CaP cements or coprecipitated during growth of CaP coatings in modified simulated body fluids (mSBF), and can achieve sustained release as the biomineral is resorbed without negatively impacting handling and surgical applicability.…”
Section: Introductionmentioning
confidence: 99%